A Review on Stuttering and Social Anxiety Disorder in Children: Possible Causes and Therapies/Treatments - Nathania, Nadia (Beyond Words, 2016)
In the past two decades, stuttering and its relation to social anxiety disorder have been researched using different approaches in study fields such as neurolinguistics and neuropsychology. This paper presents a review of research publications about social anxiety disorder in children who stutter. It takes into account studies of stuttering, social anxiety disorders, the possible causes as well as atti-tudes and beliefs towards stuttering. Also, therapies or treatments that have been conducted on both English-speaking children who stutter in the Western context and Mandarin-speaking children stut-terers in Asia, Taiwan in particular; will be looked at